SIMULTANEOUS DETERMINATION OF CONTENTS OF THREE ACTIVE COMPONENTS IN JIEJIA TINCTURE BY HPLC METHOD - Kun, Li; Fei, Wang; Yun-Peng, Diao; Xiao-qiu, Pan; Yun-Juan, E; Huo-Li, Zhang (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of the study was to determine the contents of three active components in Jiejia tincture by establishing HPLC method. Test articles were prepared by ultrasonic extraction. Separation was performed using a Kromasil C18 (250 mm × 4.6 mm, 5 μm) chromatographic column, and gradient elution was performed with acetonitrile-0.3% phosphoric acid solution as the mobile phase at a volumetric flow rate of 0.80 mL/min. The contents of catechin, baicalin and berberine in Jiejia tincture were determined at the wavelength of 276 nm and a column temperature of 30 ℃. The results revealed that catechin showed a good linear relationship at the range of 100 800 μg/mL (r=0.9997); baicalin showed a good linear relationship at the range of 15 120 μg/mL (r=0.9996), and berberine at the range of 7 56 μg/mL (r=0.9995). Their average recovery rates were 99.67% (RSD 1.01%, n=6), 98.7% (RSD 1.93%, n=6) and 100.5% (RSD 2.88%, n=6) respectively. The study concluded that the high-performance liquid chromatography established in this study was simple, accurate and reproducible, and can also be used in the determination of catechin, baicalin and berberine contents in Jiejia tincture.